Cleavage-Responsive Biofactory T Cells Suppress Infectious Diseases-Associated Hypercytokinemia - Kim, Hyelim; Son, Boram; Seo, Eun U.; Kwon, Miji; Ahn, June Hong; Shin, Heungsoo; Song, Gyu Yong; Park, Eun Ji; Na, Dong Hee; Cho, Seung-Woo; Kim, Hong Nam; Park, Hee Ho; et al. (Wiley-VCH Verlag, 2022)
Severe infectious diseases, such as coronavirus disease 2019 (COVID-19), can induce hypercytokinemia and multiple organ failure. In spite of the growing demand for peptide therapeutics against infectious diseases, current small molecule-based strategies still require frequent administration due to limited half-life and enzymatic digestion in blood. To overcome this challenge, a strategy to continuously express multi-level therapeutic peptide drugs on the surface of immune cells, is established. Here, chimeric T cells stably expressing therapeutic peptides are presented for treatment of severe infectious diseases. Using lentiviral system, T cells are engineered to express multi-level therapeutic peptides with matrix metallopeptidases- (MMP-) and tumor necrosis factor alpha converting enzyme- (TACE-) responsive cleavage sites on the surface. The enzymatic cleavage releases gamma-carboxyglutamic acid of protein C (PC-Gla) domain and thrombin receptor agonist peptide (TRAP), which activate endothelial protein C receptor (EPCR) and protease-activated receptor-1 (PAR-1), respectively. These chimeric T cells prevent vascular damage in tissue-engineered blood vessel and suppress hypercytokinemia and lung tissue damages in vivo, demonstrating promise for use of engineered T cells against sepsis and other infectious-related diseases.